Impact of Abiotic Factors on the Population Dynamics of Major Sucking Insect Pests on Bitter Gourd and Sponge Gourd - Muqeet, Abdul; Nouman, Muhammad; Bheekh, Shah Muhammad; Abbas, Samar (American Journal of Botany and Bioengineering, 2025)
This study focused on the impact of different pests on bitter gourd and sponge gourd cultivation. The pest infestation of aphids, jassids, and whiteflies was investigated on bitter gourd (variety: Prachi) and Rama tori (a hybrid variety of sponge gourd). The experiment involved investigating a simple correlation between pest populations and various abiotic factors, with four repetitions. Weekly data collection involved counting the pests on 15 randomly selected plants in each sub-block using visual observation and hand lens examination. Correlation analysis revealed significant associations between pest populations and meteorological factors such as temperature, humidity, and rainfall. For sponge gourd, aphids (-0.31*) and jassids (-0.236*) were negatively correlated with maximum temperature, but whiteflies (0.22*) were positively correlated with maximum temperature. All pests, like aphids (-0.12*), jassids (-0.1327*), and whiteflies (-0.3382*), were negatively correlated with minimum temperature. Aphids (-0.2892) and jassids (-0.0891) were negatively correlated with relative humidity. However, whiteflies showed a positive correlation with relative humidity (0.1398*). In terms of rainfall, aphids (-0.1712*), jassids (-0.1574*), and whiteflies (-0.1027*) were negatively correlated with rainfall. Similarly, for bitter gourd, aphids (-0.187*), jassids (-0.264*), and whiteflies (-0.292*) were negatively correlated with maximum temperatures, while whiteflies (0.0041*) were positively correlated with relative humidity. Aphids (-0.031*) and jassids (-0.021*) were negatively correlated with minimum temperature. In terms of rainfall, aphids (-0.2125*), jassids (-0.0257*), and whiteflies (-0.0157*) were negatively correlated with rainfall.